Case of the topsy-turvy toy - Rosenberg, Aaron; Harrington, David, 1964- (New York : Price Stern Sloan, 2011)
Nine-year-old Pete and eleven-year-old Penny Pizzarelli help their friends, toy shop owners Rupert and Eliott Jest, solve puzzles as part of a contest at the annual toy fair, but someone is trying to stop them.
3.1
K-3
K-3
470
Keywords: Contests -- Juvenile fiction; Toys -- Juvenile fiction; Puzzles -- Juvenile fiction; Swindlers and swindling -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Literary recreations; Contests -- Fiction; Toys -- Fiction; Puzzles -- Fiction; Swindlers and swindling -- Fiction; Brothers and sisters -- Fiction; Literary recreations; Mystery and detective stories; Contests -- Fiction; Toys -- Fiction; Puzzles -- Fiction; Swindlers and swindling -- Fiction; Siblings -- Fiction; Literary recreations; Mystery fiction; Mystery fiction